Late-Onset Neutropenia in Long-Term Clozapine Use and Its Management Utilizing Prophylactic G-CSF - Eimear O’ Neill; Deirdre Carolan; Sarah Kennedy; Sandra Barry (Case Reports in Psychiatry)
This case outlines recurrent neutropenia after fourteen years of successful clozapine use. The patient has a diagnosis of treatment-resistant schizophrenia which has been complicated by sensitivity to side effects of haloperidol and past failure of antipsychotics to manage her symptoms. It was necessary for our patient to follow a complicated treatment path involving close monitoring of blood levels, admissions, the initiation of lithium and the regular use of filgrastim (Neupogen), granulocyte colony stimulating factor (G-CSF). Following a failure of rescue filgrastim to increase her neutrophil levels, a management protocol was designed with input from the on-site hematology team. This protocol involved the use of filgrastim on a regular prophylactic basis. This management plan has worked for the patient who has been able to continue use of clozapine and has not suffered from any neutropenic episodes in over six months.